Simian virus 40 and human pleural mesothelioma - Mulatero, C (BMJ Group, 1999)
BACKGROUND—An aetiological role for Simian virus 40 (SV40) in malignant mesothelioma has been suggested from studies in the USA and the UK but results have been conflicting. A study was undertaken to look for evidence of SV40 in stored tissue samples from pleural mesotheliomas. METHODS—DNA was extracted from paraffin embedded tissue. The presence of DNA was established by amplification of a 250 bp product from the betaglobin gene. Primers PYV.F and PYV.R were used in a concentration of 50 per mol each per reaction to amplify a 172bp fragment of a conserved region of SV40 that codes for a portion of large T antigen that is common to SV40 and other polyoma viruses. RESULTS—Twelve of the 17 samples contained amplifiable betaglobin DNA. None of the samples (0/12, 95% CI 0 to 26.5%) was positive for the polyoma large T antigen. CONCLUSIONS—These results do not lend any support to the hypothesis that SV40 infection may be aetiologically relevant to the increasing incidence of mesothelioma in the UK.